Modulation of innate and learned sexual behaviors by the TRP channel Painless expressed in the fruit fly brain: behavioral genetic analysis and its implications - Sato, Shoma; Kitamoto, Toshihiro; Sakai, Takaomi (Frontiers in Behavioral Neuroscience, 2014)
Transient receptor potential (TRP) channels have attracted considerable attention because of their vital roles in primary sensory neurons, mediating responses to a wide variety of external environmental stimuli. However, much less is known about how TRP channels in the brain respond to intrinsic signals and are involved in neurophysiological processes that control complex behaviors. Painless (Pain) is the Drosophila TRP channel that was initially identified as a molecular sensor responsible for detecting noxious thermal and mechanical stimuli. Here, we review recent behavioral genetic studies demonstrating that Pain expressed in the brain plays a critical role in both innate and learned aspects of sexual behaviors. Several members of the TRP channel superfamily play evolutionarily conserved roles in sensory neurons as well as in other peripheral tissues. It is thus expected that brain TRP channels in vertebrates and invertebrates would have some common physiological functions. Studies of Pain in the Drosophila brain using a unique combination of genetics and physiological techniques should provide valuable insights into the fundamental principles concerning TRP channels expressed in the vertebrate and invertebrate brains.